Employability Skills Needed in the Emerging Global Job Market: Stakeholders’ Perception - Gopalakrishnan SOUNDARARAJAN; Stephen ARO-GORDON; Anitha RAVIKUMAR; Drishti Rupesh JESRANI (Communications of International Proceedings, 2020)
In the 21st century, companies all around the world have formed a higher expectation from the labours in the market. The recruitment needs by the employers for employment have changed drastically, and are not what the used to be in the olden days. There is certain kind of attributes searched for in an employee. These are employability skills sets. Different stakeholders have different perspectives on employability skills. Employability skills are found to have no common definitions. Different researchers or authors define employability skills differently. Employability skills are basic skill sets that are required to help in maintaining and keeping the job for a longer period, these skills are usually personal attributes, achievement skills, and more, that help the employee to be successful in their career option. In this literature review, it is studied if, the perceptions of the stakeholders towards the employability skills are meet or not, and if so, what might be the possible reasons. Articles from different authors and researchers were reviewed for writing this literature review. Following the purpose of the study, it is taken into account, the different perceptions of employability skills by employers, higher education institutions, and employees/graduates. During the study, there were different challenges found, that were met by the employee and the employers, and its respective solutions and reasoning towards it.
Keywords: Employability skills; Stakeholders; Perception